Efektifitas Pemberian Hasil Rekomendasi Penyelidikan Komnas HAM Terhadap Dugaan Pelanggaran HAM Kepada Lembaga Negara - Rini Fitria Morfi; Arfiani Arfiani; Feri Amsari (Lareh Law Review, 2023)
Human rights are the basis of a country in forming all provisions in the life of the nation and state which are the natural rights of every human being. The establishment of the National Human Rights Commission as an independent institution, is also based on Article 28 of the 1945 Constitution of the Republic of Indonesia which confirms that; protecting, promoting, upholding and fulfilling human rights is the responsibility of the state. This article analyzes one of the functions of Komnas HAM, namely having the authority to investigate alleged cases of human rights violations and issuing recommendations based on the investigation. The purpose of this article is to find out the effectiveness of providing state institutions with the results of investigation recommendations by the National Human Rights Commission on alleged human rights violations. This article uses a research method. This type of empirical juridical research. The results of the study found that first, according to Law Number 39 of 1999 concerning Human Rights and Law Number 26 of 2000 concerning Human Rights Courts that in protecting and guaranteeing human rights, the National Human Rights Commission has a role and function of reviewing , research, counseling, monitoring, mediation, and has the authority to investigate alleged cases of gross human rights violations, as well as issue recommendations afterward. Second, the recommendations issued by Komnas HAM after the investigation was carried out were public law acts because they resulted in a legal relationship between Komnas HAM and the Government as the recipient of the recommendations and the substance of Komnas HAM's recommendations regarding the existence of a case of human rights violations and various solutions in its settlement as well as the results of recommendations issued by Komnas HAM does not have binding and coercive legal force like court decisions which have executorial value. For this reason, some recommendations from the National Commission on Human Rights were followed up by the target state agencies, some were not.